The Effect of Financial Performance, Company Size and Good Corporate Governance on Sustainability Report - Naili Saadah; Ratno Agriyanto; Warno; Putri Mustika Winda (AFEBI Accounting Review, 2020)
Companies often take advantage of existing natural resources as suppliers of the main raw materials that are processed by the company to produce products that will be sold to consumers. The environment where natural resources are located can be interpreted as the area or community around where the company operates. Of course, the company's operational activities will have an impact on the environment, both in the form of positive and negative impacts. This research uses quantitative research methods with descriptive statistical analysis techniques. While the research hypothesis testing was carried out using regression analysis. And the regression analysis used in this research is logistic regression. By using mining companies listed on the Jakarta stock exchange during the 2015-2018 period, 44 sample companies were obtained. Logistic regression test results prove that financial performance has no effect on Sustainability Report, company size has no effect on Sustainability Report, Good Corporate Governance has a significant positive effect on Sustainability Report.